Smurf1-Mediated Lys29-Linked Nonproteolytic Polyubiquitination of Axin Negatively Regulates Wnt/β-Catenin Signaling - Fei Cong; Zhenfei Li; Chen Li; Yue‐Lei Chen; Zhangcheng Chen; Xiaoli He; Li Mao; Xin Wang; Rong Zeng; Lin Li (2013)
Ubiquitination plays important and diverse roles in modulating protein functions.As a C2-WW-HECT-type ubiquitin ligase, Smad ubiquitination regulatory factor 1 (Smurf1) commonly serves to regulate ubiquitin-dependent protein degradation in a number of signaling pathways.Here, we report a novel function of Smurf1 in regulating Wnt/␤-catenin signaling through targeting axin for nonproteolytic ubiquitination.Our data unambiguously demonstrate that Smurf1 ubiquitinates axin through Lys 29 (K29)-linked polyubiquitin chains.Unexpectedly, Smurf1-mediated axin ubiquitination does not lead to its degradation but instead disrupts its interaction with the Wnt coreceptors LRP5/6, which subsequently attenuates Wnt-stimulated LRP6 phosphorylation and represses Wnt/␤-catenin signaling.The inhibitory function of Smurf1 on Wnt/␤-catenin signaling is further evidenced by analysis with Smurf1 knockout murine embryonic fibroblasts.We next identified K789 and K821 in axin as the ubiquitination sites by Smurf1.Consistently, Smurf1 could neither disrupt the interaction of an axin K789/821R double mutant with LRP5/6 nor attenuate the phosphorylation of LRP6 in axin K789/821R -expressing cells.Collectively, our studies uncover Smurf1 as a new regulator for the Wnt/␤-catenin signaling pathway via modulating the activity of axin.